The Sunday of the negative : reading Bataille, reading Hegel - Gemerchak, Christopher M. (SUNY series in Hegelian studies., 2003)
"The Sunday of the Negative provides the most extensive English-language investigation of Bataille's critical treatment of the thought of Hegel, focusing on the notions of subjectivity, desire, self-consciousness, knowledge, and the experience of the divine. The book spans all of Bataille's writings, patiently navigating even the most obscure texts. The author explains how Bataille's notion of self-consciousness both derives from, and is an alternative to, that of Hegel. Disclosing the origins of Bataille's most influential concepts, the book moves across philosophy proper to include reflections on anthropology, economics, cultural criticism, poetry, eroticism, mysticism, and religion."--Jacket